Determination of typical resilient modulus values for selected soils in Wisconsin - Helwany, Sam; Elias, Mohammed B.; Titi, Hani (Wisconsin Highway Research Program, 2006)
The objective of this research is to develop correlations for estimating the resilient modulus of various Wisconsin subgrade soils from basic soil properties. A laboratory testing program was conducted on common subgrade soils to evaluate their physical and compaction properties. The resilient modulus of the investigated soils was determined from the repeated load triaxial test following the American Association of State Highway and Transportation Officials (AASHTO) T 307 procedure. The laboratory testing program produced a high quality and consistent test results database. The high quality test results were assured through a repeatability study and also by performing two tests on each soil specimen at the specified physical conditions. The resilient modulus constitutive equation adopted by National Cooperative Highway Research Program (NCHRP) Project 1-37A was selected for this study. Comprehensive statistical analysis was performed to develop correlations between basic soil properties and the resilient modulus model parameters k sub i. The analysis did not yield good results when the whole test database was used. However, good results were obtained when fine-grained and coarse-grained soils were analyzed separately. The correlations developed in this study were able to estimate the resilient modulus of the compacted subgrade soils with reasonable accuracy. In order to inspect the performance of the models developed in this study, comparison with the models developed based on the Long-Term Pavement Performance (LTPP) database was made. The LTPP models did not yield good results compared to the models proposed by this study. This is due to differences in the test procedures, test equipment, sample preparation, and other conditions involved with development of both LTPP and the models of this study.
175 p.
Keywords: Triaxial shear tests; Test procedures; Subgrade (Pavements); Statistical analysis; Modulus of resilience; Laboratory tests; Fine grained soils; Databases; Compaction; Coarse grained soils